High-sensitivity Cardiac Troponin Elevation after Electroconvulsive Therapy: A Prospective, Observational Cohort Study. (April 2017) - Duma, Andreas; Pal, Swatilika; Johnston, Joshua; Helwani, Mohammad A.; Bhat, Adithya; Gill, Bali; Rosenkvist, Jessica; Cartmill, Christopher; Brown, Frank; Miller, J. Philip; Scott, Mitchell G.; Sanchez-Conde, Francisco; et al.
Abstract : Background: While electroconvulsive therapy is widely regarded as a lifesaving and safe procedure, evidence regarding its effects on myocardial cell injury is sparse. The objective of this investigation was to determine the incidence and magnitude of new cardiac troponin elevation after electroconvulsive therapy using a novel high-sensitivity cardiac troponin I assay. Methods: This was a prospective cohort study in adult patients undergoing electroconvulsive therapy in a single academic center (up to three electroconvulsive therapy treatments per patient). The primary outcome was new high-sensitivity cardiac troponin I elevation after electroconvulsive therapy, defined as an increase of high-sensitivity cardiac troponin I greater than 100% after electroconvulsive therapy compared to baseline with at least one value above the limit of quantification (10 ng/l). Twelve-lead electrocardiogram and high-sensitivity cardiac troponin I values were obtained before and 15 to 30 min after electroconvulsive therapy; in a subset of patients, an additional 2-h high-sensitivity cardiac troponin I value was obtained. Results: The final study population was 100 patients and a total of 245 electroconvulsive therapy treatment sessions. Eight patients (8 of 100; 8%) experienced new high-sensitivity cardiac troponin I elevation after electroconvulsive therapy with a cumulative incidence of 3.7% (9 of 245 treatments; one patient had two high-sensitivity cardiac troponin I elevations), two of whom had a non–ST-elevation myocardial infarction (incidence 2 of 245; 0.8%). Median high-sensitivity cardiac troponin I concentrations did not increase significantly after electroconvulsive therapy. Tachycardia and/or elevated systolic blood pressure developed after approximately two thirds of electroconvulsive therapy treatments. Conclusions: Electroconvulsive therapy appears safe from a cardiac standpoint in a large majority of patients. A small subset of patients with preexisting cardiovascular risk factors, however, may develop new cardiac troponin elevation after electroconvulsive therapy, the clinical relevance of which is unclear in the absence of signs of myocardial ischemia. Abstract : This prospective cohort study of 100 patients undergoing electroconvulsive therapy (ECT) demonstrated that (1) most patients did not develop a high-sensitivity cardiac troponin I (hscTnI) elevation after ECT; (2) median hscTnI values did not change after ECT, both when measured immediately and 2 h after ECT; and (3) a small subset of patients developed new hscTnI elevation after ECT, indicative of myocardial injury.